PEMBERDAYAAN KEWIRAUSAHAAN YANG BERKELANJUTAN PADA USAHA KOMUNITAS DI DESA SRUWENG-KEBUMEN, PROVINSI JAWA TENGAH - Anggraeni Permatasari; Retnowati Retnowati; A.B.M. Witono (Universitas Mataram, 2023)
The Covid-19 pandemic has significantly impacted Micro, Small, and Medium Enterprises (MSMEs), especially in rural areas. They try to increase their productivity and start their business again. MSMEs must develop positive business attitudes, opportunity reading skills, and a strong mentality. This community service program (PkM) aims to increase the entrepreneurial mindset in rural areas and revive the capacity and competitiveness of MSME actors. This program focuses on the community business group in Sruweng Village, Kebumen, Central Java. PkM activities consist of two activities such as training/workshops and processual empowerment. The total number of participants is 40, consisting of community business actors who experienced the impact of the covid-19 pandemic. The observations and FGDs found that MSME actors had several obstacles to restarting their business, including limited business capital (social and financial), production management, and marketing strategy. This activity's output has provided motivation and confidence for MSME actors to start or develop their businesses again. All participants shared experiences and solutions in dealing with the Covid-19 pandemic during the process. Through this process, participants succeeded in generating new ideas and understanding changes in market conditions after the Covid-19 pandemic. In addition, PkM activities help MSME actors improve the quality of their products and formulate effective and efficient business models and marketing strategies.